USAHA GURU PAI DALAM MEMBINA AKHLAK MELALUI PEMBELAJARAN DARING DI SD NEGERI 1 KAOBULA - Nurmin Aminu, Nurmin Aminu (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2021)
The purpose of this study was to determine the efforts of PAI teachers in fostering morals through online learning at SD Negeri 1 Kaobula. The research method used is qualitative research. Qualitative research is research that is used to examine the condition of a natural object, (as opposed to an experiment) where the researcher is the key instrument, the data collection technique is done by triangulation (combined), the data analysis is inductive/qualitative. The results of the study indicate that the efforts of Islamic religious education teachers in online learning have their own challenges in understanding students so that they remain the movers who have good morals for students, so that students in the future are more enthusiastic and active in getting morals. PAI teachers at SD Negeri 1 Kaobula are also required to have learning methods or strategies that are adapted to the current state of students, where PAI teachers provide learning with creative and innovative methods that can motivate students to have good morals